Novel nickel-immobilized-SiO2-TiO2 fine particles in the presence of cetyltrimethylammonium bromide as a catalyst for ultrasound-assisted-Kumada cross-coupling reaction - Dewi Agustiningsih; Eko Sri Kunarti; Nuryono Nuryono; Sri Juari Santosa; Muhammad Idham Darussalam Mardjan; Yuichi Kamiya; Ryoichi Otomo (Heliyon, 2024)
Kumada cross-coupling reaction is useful for producing biphenyls, where nickel and copper have been widely investigated as catalysts but mainly homogeneous ones. In this study, we investigated ultrasound-assisted-Kumada cross-coupling reaction over the heterogeneous catalysts in which Ni2+, Cu2+, or both was immobilized on aminopropylsilane-functionalized-SiO2-TiO2 prepared in the presence of cetyltrimethylammonium bromide (CTAB). The presence of CTAB effectively prevented the particle growth and therefore SiO2–TiO2 fine particles with high surface area (502 m2 g−1) were formed. The Ni2+-immobilized catalyst showed high catalytic activity for the ultrasound-assisted-Kumada cross-coupling reaction of a wide variety of substrates and was reusable three times. Performing the reaction under ultrasound irradiation was very effective in significantly accelerating the reaction rate compared with the conventional mechanical method. In contrast to Ni2+, Cu2+ was deposited on the support as crystalline Cu(OH)2 and the resulting catalysts with Cu2+ and Ni2+-Cu2+ were less active and less stable under the reaction conditions.